The behavioural lens: Taking a behavioural vantage point to improve the success of development programmes - Lennart Kaplan; Sascha Kuhn; Jana Kuhnt (Deutsches Institut für Entwicklungspolitik (DIE), 2020)
Successful programmes and policies require supportive behaviour from their targeted populations. Understanding what drives human reactions is crucial for the design and implementation of development programmes. Research has shown that people are not rational agents and that providing them with financial or material incentives is often not enough to foster long-term behavioural change. For this reason, the consideration of behavioural aspects that influence an individual's actions, including the local context, has moved into the focus of development programmes. Disregarding these factors endangers the success of programmes. The World Bank brought this point forward forcefully with its 2015 World Development Report, "Mind, Society and Behavior", herewith supporting the focus on behavioural insights within development policies. While agencies may intuitively consider behavioural aspects during programme design and implementation, a systematic approach would improve programme effectiveness at a relatively small financial cost. For this reason, we present a framework - the Theory of Planned Behaviour (TPB) (Ajzen, 1991) - that aids practitioners and researchers alike in considering important determinants of human behaviour during the design and implementation of development programmes The TPB suggests considering important determinants of human behaviour, such as the individual's attitude towards the intervention (influenced by previous knowledge, information or learning); subjective norms (influenced by important people, such as family members or superiors); and the individual's sense of behavioural control (influenced by a subjective assessment of barriers and enablers). The theory should be used early on in the programme design to perform a structured assessment of behavioural aspects in the appropriate context. Components of the TPB can often be addressed through cost-effective, easy changes to existing programmes. Simple guiding questions (see Box 1) can help integrate the theory into the programme design. An iterative and inclusive process, particularly in exchange with the targeted population and other stakeholders, increases success.
Keywords: 330